Ecological Load and Balancing Selection in Circumboreal Barnacles. (8th September 2020) - Nunez, Joaquin C B; Rong, Stephen; Damian-Serrano, Alejandro; Burley, John T; Elyanow, Rebecca G; Ferranti, David A; Neil, Kimberly B; Glenner, Henrik; Rosenblad, Magnus Alm; Blomberg, Anders; Johannesson, Kerstin; Rand, David M
Abstract: Acorn barnacle adults experience environmental heterogeneity at various spatial scales of their circumboreal habitat, raising the question of how adaptation to high environmental variability is maintained in the face of strong juvenile dispersal and mortality. Here, we show that 4% of genes in the barnacle genome experience balancing selection across the entire range of the species. Many of these genes harbor mutations maintained across 2 My of evolution between the Pacific and Atlantic oceans. These genes are involved in ion regulation, pain reception, and heat tolerance, functions which are essential in highly variable ecosystems. The data also reveal complex population structure within and between basins, driven by the trans-Arctic interchange and the last glaciation. Divergence between Atlantic and Pacific populations is high, foreshadowing the onset of allopatric speciation, and suggesting that balancing selection is strong enough to maintain functional variation for millions of years in the face of complex demography.